Does social capital dimensions foster innovation capabilities? - Grieco, Antonio Augusto de Miranda (2017)
Innovation is considered one of the key capabilities required for organizations to achieve success. Previous research has claimed that social capital influences innovation capabilities, yet not the extent of its dimensions (cognitive, relational and structural). This study addressed this research gap by a survey performed among ANPEI (Research and Development Nacional Association of Innovative Companies) members, specifically innovation managers from Brazilian and multinational companies from several sectors, operating in Brasil. 440 innovation managers from 220 companies during the period from December/2016 and January/2017 participated. An instrument with 24 items was designed to measure the independent and dependent variables. A web-based survey was created on QuestionPro Platform, to disseminate the survey through a link and collect data easily. The software SmartPLS 3 was used to treat the data as main analysis tool. It estimates PLS path models for the empirical validation of Theoretical model. The results showed that both cognitive, relational and structural dimensions of social capital affect positvelly the generation of innovation capability, but we found out that the structural social capital has a higher impact on the generation of innovation capability. We verified that R&D also affects positevly in the generation of Innovation Capability.